Nitrogen use efficiency as a tool to evaluate the development of ornamental cacti species - Silva,Karina Gonçalves da (2017)
ABSTRACT Nitrogen efficiency, along with associated indexes, is a widely used tool for assessing nutritional status in agricultural species. However, this parameter is not used in studies with ornamental plants, especially epiphytic cacti species. In particular, we know very little about the potential response of ornamental cacti to N absorption and use. Therefore, this study aimed to evaluate N use efficiency (NUE), along with its associated parameters, in three species of ornamental cacti under nitrogen nutrition. To accomplish this, Rhipsalis baccifera, Rhipsalis paradoxa and Hatiora salicornioides were fertilized by Hogland and Arnon nutrition solution modified and enriched with urea in the concentrations of 0, 33.3 or 66.6 mM N during 180 days. At the end of the experiment, efficiency indexes were calculated. Efficiency parameters varied according to species. R. baccifera presented the greatest dissimilarity among the species, with highest uptake efficiency (NUpE), but lowest use efficiency (NUtE) and biomass conversion (BCE). R. paradoxa presented high values for NUE, NUtE, BCE and physiological efficiency (NPE) at concentrations of 33.3 mM N, suggesting greater investment in biological processes with lower supply of N. H. salicornioides had the highest averages in most parameters measured. Our results show that these indexes provided important comparative baseline information on nutritional status and investment strategy, thus serving as a suitable analytical tool to increase knowledge about this group of ornamental plants.